PENGARUH KARBON MONOKSIDA TERHADAP OZON PERMUKAAN - Novita Ambarsari; Ninong Komala; Afif Budiyono (Widyariset, 2010)
Surface ozone is one of air pollutant that can be very dangerous for human health and many other aspects of the living things. The effect of carbon monoxide (CO) to surface ozone formation has been studied. We used Dasibi Monitor Ozone and Horiba Ambient Carbon Monoxide Monitor to measure surface ozone and carbon monoxide concentration at air pollution monitoring station belong to LAPAN Bandung along 2008. The result shows that carbon monoxide affecting 20%–80% formation of surface ozone with negative correlation. A normal photochemical reaction is the main factors. Daily variation of surface ozone shows lower concentration occur in the morning and night, and higher concentration occur in the evening. While, daily variation of CO shows maximum concentrationin the morning and night, and lower in the evening.